2007
DOI: 10.1016/j.cplett.2007.01.077
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution two-dimensional NMR spectra of half-integer-spin quadrupolar nuclei from one-dimensional projections

Abstract: We present a technique providing high-resolution spectra of quadrupolar nuclei with half-integer nuclear spin displaying significant second-order linebroadening. The technique, dubbed chemical shift-quadrupolar projection-reconstruction of one-dimensional spectra (CQ-PRODI) exploits the different magnetic field dependence of the chemical shift and second-order quadrupolar effect. Onedimensional spectra recorded at different magnetic field strengths are represented as projections along different directions in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…The MQMAS experiment is meanwhile one of the most frequently applied techniques for the investigation of quadrupolar nuclei (see below). In 2007 Vosegaard and Massiot developed a method called “chemical shift-quadrupolar projection-reconstruction of one-dimensional spectra” (CQ-PRODI [ 83 ]). CQ-PRODI is based on the correlation of chemical shifts with the second-order quadrupolar line shapes from multiple spectra recorded at different B 0 strengths, which allows the construction of high-resolution spectra.…”
Section: Characterization Of the Mof Latticementioning
confidence: 99%
“…The MQMAS experiment is meanwhile one of the most frequently applied techniques for the investigation of quadrupolar nuclei (see below). In 2007 Vosegaard and Massiot developed a method called “chemical shift-quadrupolar projection-reconstruction of one-dimensional spectra” (CQ-PRODI [ 83 ]). CQ-PRODI is based on the correlation of chemical shifts with the second-order quadrupolar line shapes from multiple spectra recorded at different B 0 strengths, which allows the construction of high-resolution spectra.…”
Section: Characterization Of the Mof Latticementioning
confidence: 99%
“…In solid-state NMR, isolated attempts to use single-scan and projection-reconstruction spectroscopy have been presented [18][19][20]. A broad application of these techniques is however limited due to the low sensitivity of the heteronuclei detection usually used in solidstate NMR.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, for powdered samples it has been necessary to use advanced techniques such as dynamic-angle spinning to achieve site-specific resolution [96]. We later proposed a projectionreconstruction method that used one-dimensional spectra from different magnetic field strengths to reconstruct a two-dimensional correlation experiment with spectral resolution [97]. Most interestingly, Hung and Gan recently demonstrated that by using low-power STMAS it is now possible to resolve such sites, which seems to be of broad applicability [98].…”
Section: Gallium-69 and -71 Single-crystal Nmrmentioning
confidence: 99%